2007
DOI: 10.1186/1471-2202-8-34
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of TAC1, PENK and SOCS2 in Hcrtr-2 mutated narcoleptic dog brain

Abstract: Background: Narcolepsy causes dramatic behavioral alterations in both humans and dogs, with excessive sleepiness and cataplexy triggered by emotional stimuli. Deficiencies in the hypocretin system are well established as the origin of the condition; both from studies in humans who lack the hypocretin ligand (HCRT) and in dogs with a mutation in hypocretin receptor 2 (HCRTR2). However, little is known about molecular alterations downstream of the hypocretin signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…The finding that OX increases gene expression and peptide levels of SP in this subregion is the first direct evidence for a close relationship between these neuropeptides. This is consistent with indirect evidence, showing that a mutation of OX2R decreases gene expression of tachykinin precursor 1 (Lindberg et al ) and that OX1R exists on SP‐containing dorsal root ganglion neurons (Colas et al ). The smaller increase in SP peptide relative to mRNA levels may reflect the difference in the timing of their measurement, with levels possibly higher shortly after OX injection.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The finding that OX increases gene expression and peptide levels of SP in this subregion is the first direct evidence for a close relationship between these neuropeptides. This is consistent with indirect evidence, showing that a mutation of OX2R decreases gene expression of tachykinin precursor 1 (Lindberg et al ) and that OX1R exists on SP‐containing dorsal root ganglion neurons (Colas et al ). The smaller increase in SP peptide relative to mRNA levels may reflect the difference in the timing of their measurement, with levels possibly higher shortly after OX injection.…”
Section: Discussionsupporting
confidence: 90%
“…This neuropeptide may have similar actions in the PVT, where it has been detected in perikarya and fibers (McLean, Skirboll & Pert ; Battaglia, Spreafico & Rustioni ) and NK1R has also been described (Mantyh, Hunt & Maggio ). The idea that SP in the PVT may function in close relation to OX is suggested by the finding that expression of tachykinin precursor 1, which encodes SP, is enhanced in the amygdala of dogs with a mutation of OX2R (Lindberg et al ) and that OX1R in rats is expressed on SP‐containing dorsal root ganglion neurons (Colas et al ). These studies hint at the possibility that SP may function in close relation to OX, acting in the PVT to stimulate ethanol drinking.…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion is further supported by the recent finding that central injection of GAL or OX can stimulate endogenous expression of ENK in the PVN (Karatayev et al, 2009). In addition, one study using microarray technology has identified preproENK as one of only three molecules specifically down-regulated in the brain by a mutation of the OX 2 receptor (OX 2 R) in narcoleptic dogs (Lindberg et al, 2007). Together, these results indicate that the non-opioid peptides in the PVN, both GAL-expressing neurons and OX innervation to the nucleus, may be important regulators of local ENK, functioning through this opioid to stimulate feeding and mediating upstream the stimulatory effect of a HFD on endogenous ENK.…”
mentioning
confidence: 99%
“…Some silico analysis implied that some important molecular signaling pathway such as IP3 pathway, IGF1R pathway, cAMP pathway may be associated with cognitive enhancement in animal models of brain disease (Jellen et al 2015 ). Based on previous research, it is suggested that TAC1 , PENK and SOCS2 might be intimately connected with the excessive daytime sleepiness not only in dogs, but also in other species, possibly including humans (Lindberg et al 2007 ). Other studies revealed that the diagnosis of narcolepsy but not CPT1B expression level was associated with abnormally and significantly low acylcarnitine levels (Miyagawa et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%